Pembrolizumab-combination therapy for previously untreated metastatic nonsquamous NSCLC: Real-world outcomes at US oncology practices - Liu, Stephen V.; Hu, Xiaohan; Li, Yeran; Zhao, Bin; Burke, Thomas; Velcheti, Vamsidhar (Frontiers in Oncology, 2022)
Objectives: The availability of immunotherapies has expanded the options for treating metastatic NSCLC, but information is needed regarding outcomes of immunotherapy for patients treated outside of clinical trials. The aim of this retrospective study was to evaluate the outcomes of therapy with first-line pembrolizumab plus pemetrexed and carboplatin (pembrolizumab-combination) for patients with metastatic nonsquamous NSCLC in the real-world setting of oncology clinics in the United States (US). Methods: Using deidentified, longitudinal patient records from a nationwide, electronic health record-derived US database, we identified patients with metastatic nonsquamous NSCLC, without EGFR/ALK/ROS1 genomic alterations, who had received no previous systemic anticancer therapy. Eligible patients had an Eastern Cooperative Oncology Group (ECOG) performance status of 0 or 1 and initiated first-line pembrolizumab-combination therapy from 11-May-2017 to 31-January-2019; data cutoff was 31-August-2020. Patients treated in a clinical trial were excluded. Manual chart review supplemented technology-enabled abstraction to identify disease progression and tumor response. Time-to-event endpoints from initiation of pembrolizumab-combination therapy were determined using Kaplan-Meier. Results: Of 377 patients with metastatic nonsquamous NSCLC, 105 (28%), 104 (28%), and 103 (27%) had programmed death-ligand 1 (PD-L1) expression ≥50%, 1–49%, and <1%, respectively; PD-L1 expression was not documented for 65 patients (17%). Median age was 66 years, and 227 patients (60%) were men. Median follow-up time from first-line therapy initiation to data cutoff was 31.2 months (range, 19.0-39.6 months). Median pembrolizumab real-world time on treatment (rwToT) was 5.8 months (95% CI, 5.0-6.7); 12- and 24-month on-treatment rates for pembrolizumab were 28.0% and 14.9%, respectively. Median overall survival (OS) was 17.2 months (95% CI, 13.6-19.9). For patients in PD-L1 expression ≥50%, 1-49%, <1%, and unknown cohorts, the 12-month survival rates were 66.0%, 58.5%, 54.5%, and 58.3%, respectively, and 24-month survival rates were 43.1%, 37.2%, 35.6%, and 42.0%, respectively. Median real-world progression-free survival was 6.2 months (95% CI, 5.5-7.1); and the real-world response rate was 39.3%, with median duration of response of 13.1 months (95% CI, 10.5-16.8). Conclusions: These findings demonstrate the benefits of first-line pembrolizumab-combination therapy for patients with EGFR/ALK-wild-type, metastatic nonsquamous NSCLC and good performance status who are treated at US community oncology clinics.